Challenges of E-learning in Medical Sciences: A Review Article - mahim naderifar; fereshtehghaljaie; alia jalalodini (Zanjan University of Medical Sciences and Health Services, 2017)
Background and objective: Extension of knowledge and information is given a new meaning to the concept of education. One of The most important reasons for the use of e-learning in medical education is that learning is learned by the learners themselves. This method facilitates their individualized education programs. This study introduced the challenges and solutions for the achievement of e-learning in medical education. Materials and Methods: This is a review article that was implemented a comprehensive review using the World Wide Web. The databases such as Medline, Ovid, ProQuest, and PubMed as well as key words "e-learning, educational challenges and medical education" in Persian and English languages were used. Of the 80 articles fund, 30 articles which were related to the research objective were chosen. Results: The research showed that e-learning, despite its advantages and wide applications, has drawbacks including the lack of implementation by lecturer due to lack of knowledge of its functioning, the fading role of lecturer, lack of expertise in its application, fear of its application, special cultural beliefs and insufficient resources. Conclusion: It is necessary to consider establishing standards and substructures for achieving the implementation of e-learning in medical education. Because of inexperience of universities of medical sciences in Iran compared with other universities around the world, we suggest using the experience of universities in other countries. Also holding workshops based on e-learning can be effective.